UiTM Sarawak at The International Level - Kipli, Nur Aida; Ramakrishnan, Prabha; Maniam, Yuthandy; Abdullah, Norazlin; Jack, Suriani; Abg Samah, Aizimah; Chiew, Fei Ha (Universiti Teknologi MARA, Sarawak, 2009)
The display highlights UiTM Sarawak's achievements at international innovation events, where research team earned Silver and Gold medals in Moscow, London and Geneva. The recognition reflects the university's strong presence, commitment to research excellence, and ability to compete on the global stage.